2019
DOI: 10.1016/j.aott.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic outcomes of open reduction and internal fixation for cementless stems in Vancouver B2 periprosthetic fractures

Abstract: ObjectiveThe aim of this study was to evaluate the radiologic outcomes of open reduction and lateral plating with wiring in the treatment of Vancouver B2 periprosthetic femoral fractures.MethodsWe retrospectively recruited 37 patients treated with ORIF with lateral plating and wiring for Vancouver B2 fractures. The 27 patients (15 men and 12 women; mean age: 70.8 ± 8.3 years) without follow-up loss had achieved complete bony union without notable complications. The average union period was checked after operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…However, there was no case with loss of reduction or loss of fixation requiring revision surgery. 33 We presume that with fixation devices such as locking attachment plates and cerclage wires, the osteosynthesis gets further rigidity, and the stem regains stability. Severe subsidence of the prosthesis that leads to persistent pain and revision operations can thereby be avoided in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no case with loss of reduction or loss of fixation requiring revision surgery. 33 We presume that with fixation devices such as locking attachment plates and cerclage wires, the osteosynthesis gets further rigidity, and the stem regains stability. Severe subsidence of the prosthesis that leads to persistent pain and revision operations can thereby be avoided in the majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies published case-by-case data in the form of a table. 14,25,28,29,31,32 All of the included studies were retrospective and all but 2 reported data from a single institution. 10,30 Analysis of the funnel plot calculated using the complication data indicated no evidence of publication bias (see…”
Section: Study Qualitymentioning
confidence: 99%
“…Despite emerging observational data on the role of ORIF in B2 management, the overall efficacy and safety are yet to be established in part because of the small sample sizes. 14,15 As such, a systematic review and meta-analysis was designed to establish the current evidence for ORIF in Vancouver B2 patients compared with conventional revision arthroplasty (rTHA). We hypothesized that rTHA as the traditional approach to this problem has more favorable outcomes compared with ORIF in context of a PFF with adequate bone stock and a loose femoral stem.…”
Section: Introductionmentioning
confidence: 99%
“…Subgroup analysis of complications in type-B2 fractures included results from 9 studies 17,20,27,[33][34][35][36][37][38] (27.3%) and involved 104 ORIFtreated and 148 RA-treated patients with a mean follow-up of 3.1 years and 3.5 years, respectively. Again, no significant difference between the 2 groups was observed (21% versus 26%; p 5 0.647).…”
Section: Complication Ratesmentioning
confidence: 99%